1986
DOI: 10.1088/0022-3727/19/12/013
|View full text |Cite
|
Sign up to set email alerts
|

The role of impurities on the deviation from Paschen's law of SF6

Abstract: Deviations to Paschen's law for SF6 at high pressures are commonly explained by field enhancement due to protrusions supposed to exist at the surface of the electrodes. New experiments for positive polarity allow the authors to draw a different conclusion, i.e. to ascribe these deviations to the impurities of the gas, especially to the combined effect of O2 and H2O. For negative polarity, impurities play a minor role and the threshold is very sensitive to the surface state of the stressed electrode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 2 publications
2
15
0
Order By: Relevance
“…This situation is a direct consequence of the fact that the experimental A.value is very dependent on the absolute accuracy of the voltage measurement, while the corresponding B value is only dependent on the relative accuracy of this measurement. Although no information about these measurement accuracies is given by Berger and Senouci [7], the relative accuracy is generally much better than the absolute accuracy. In relation to the A values of Table 1 it should be noted that A (Paschen) is only 0.35 kV [16].…”
Section: Ieee !Lkansactions On Electrical Insulationmentioning
confidence: 99%
See 4 more Smart Citations
“…This situation is a direct consequence of the fact that the experimental A.value is very dependent on the absolute accuracy of the voltage measurement, while the corresponding B value is only dependent on the relative accuracy of this measurement. Although no information about these measurement accuracies is given by Berger and Senouci [7], the relative accuracy is generally much better than the absolute accuracy. In relation to the A values of Table 1 it should be noted that A (Paschen) is only 0.35 kV [16].…”
Section: Ieee !Lkansactions On Electrical Insulationmentioning
confidence: 99%
“…With reference to strongly electronegative gases, it is found that upon application of the streamer criterion to the above field distribution one obtains and - (7) see [ll, 141 for details. The parameter M represents the figure of merit for a strongly electronegative gas (121, while Hso is the normalized critical avalanche length.…”
Section: Surface Curvature Factor Cmentioning
confidence: 99%
See 3 more Smart Citations